The Nutritional Requirement of Anoa - Abdul Haris Mustari; Burhanuddin Masy'ud (Media Konservasi, 2001)
The objective of the study was to obtain the food preference, food intake, digestibility and the protein requirement of anoa. Two kind of fwd (ration) were offered to the animal in Ragunan Zoo: the single ration of Pennisetum purpureum and the mixed grasses of Pennisetum purpureum. Cyrtococcum patens, Mikania cordata and Costus speciocus with the composition of 25 %, respectively. The result showed that the daily food intake of anoa in the zoo was 4.49-7.03 kg (average 5.98 kg) for Pennisetum purpereurn and 6.74-10.33 kg (average 8.12 kg) for the mixed grasses. Based on the body weight, the food intake of the animals was 8.34 % to 11.54 %. The animals showed the higher preference for feeding on the mixed grasses. The food digestibility was 92 % - 96.68 % for Pennisetum purpureum and 82.88% - 92.71 % for the mixed grasses. Protein requirment of the animals were 15.20-29.72 gr per day. The high preference on the mixed grasses has closely related to the natural habit of the animals that consume a varity of plants. This animals showed preference as browser than grazers.